SOCIAL CAPITAL OF HUMAN RESOURCES IN SMES ON COMPETITIVE ADVANTAGES - Badriyah, Nurul (Jurnal Aplikasi Manajemen, 2017)
Fundamental change in the business environment is characterized by the volatility of business environment. Business condition is increasingly complex and unpredictable for organizations which want to achieve competitive advantage. Social capital is the attitude shown through more convincing communication and knowledge. Good social capital ownership is the form of human resources’ competence in empowering and optimizing the business management for the survival of company. The objectives of this study are to identify and explain the significant effect of social capital of human resources in SMEs on competitive advantages. Research method used in this research is quantitative (positivistic) with analysis tool of exel program aid and GSCA software. Research respondents are 74 (seventy four) entrepreneurs of small and medium enterprises which have been clustered as the largest SMEs in each regency by Department of Industry and Trade in East Java in 2015. From the research results, it can be concluded that: (1) Social interaction significantly influences competitive advantage, with loading rate of 0.705. (2) Social action has significant effect on competitive advantage, with loading rate of 0.802 (3) Social Capital simultaneously has significant effect on competitive advantage and is considered to be able to exploit and neutralize threats from outside the company. (4) Social action is considered the most dominant effect on competitive advantages with results of path analysis of 0.93. Therefore, it can be suggested that: (1) Social interaction should be developed because it is able to measure consumer initiatives to be more productive socially. (2) Human resource development for entrepreneurs in order to improve social behavior can be done by training. (3) Government should promote training to improve the behavior of social capital.